Acid-base evaluation of chitosan-ferulic acid conjugate by a free radical grafting method. (March 2019) - Anwar, M; Nisa, K; Indirayati, N
Abstract: Chitosan-ferulic acid conjugate has been synthesized based on the free radical-mediated grafting reaction. This study investigated the application of potentiometric titration to evaluate the free radical grafting method of ferulic acid on chitosan. The synthesis was done by hydrogen peroxide/ascorbic acid induced free radical reaction to conjugate ferulic acid with chitosan. The conjugate product of ferulic acid-chitosan was characterized by FTIR, UV-Vis spectrophotometry, potentiometric titration, and SEM images. Evaluation of the grating ratio of the ferulic acid-g-chitosan was determined by Folin–Ciocalteu method. The chitosan-ferulic acid conjugate gave 84% in yield with total phenolic showed the value was 92 .53 mg per gram of dry polymers and the conjugate product only soluble at pH around 6. The antioxidant activity of chitosan was increased after functionalized with ferulic acid.